Study of Approaches to Forecasting the State Budget and Methods of Planning Its Macroeconomic Indicators - Butenko, Olena; Opikunova, Nataliya (Theory and Practice of Public Administration, 2019)
Budget planning and forecasting are one of the tools for ensuring a stable economic and social development of the state. At present, the method of budget forecasting and planning needs to be improved through a series of tasks identi ed by the current political and economic situation in the country. The paper objective is the study and assessment of the existing method of budget forecasting to determine compliance with modern requirements. The paper main body. To this end, in the article, while relying on the task of the “Strategy of reforming the system of management of public  nances” adopted on February 8, 2017, which indicates the need to strengthen the institutional capacity of the Ministry of Economic Development and the Ministry of Finance in the  eld of forecasting, in particular, macro indicators and budget indicators, methods have been investigated, which are currently used to calculate the medium-term budget in order to determine their advantages and disadvantages and compliance with certain contemporary requirements. It is established that due to a number of characteristic features of each method, the  nal calculation method is chosen after an assessment of the situation that has developed in the corresponding period. It has been established that all methods must be interconnected, they must compensate for the shortcomings of each one and bene t from them, so the process of developing such plans is very laborious. It has been established that the methods of forecasting the macroeconomic indicators of the state budget foresee the calculation of planned indicators, based on past periods, norms regulating types of incomes and expenditures, optimize limited budget resources, generate the necessary amount of income, but there are, according to the author, some drawbacks that need research and elimination.